Instructing and mentoring ex-con university students in departments of criminology and criminal justice - Tewksbury, Richard (Corrections, 2019)
Recognizing the growing presence of university students who arealso ex-cons, this article discusses the challenges of working withsuch individuals and offers practical suggestions for ways to enhancesuch interactions. The effects of institutional socialization, culturaldifferences, and a range of abilities and motivations presented by ex-con students requires a need to design and implement uniqueinstructional, especially mentoring, approaches that are most likelyto be successful.